CONGENITAL HYPOTHYROIDISM IN A TWIN MISSED BY NEWBORN SCREENING: A CASE REPORT - Kejendaram, Shemalatha; Hwu, Ting Tzer; Lin, Lee Yee (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Thyroid hormone plays a significant role in the development of multiple organ systems especially the brain. Newborn screening program enables early detection and treatment of congenital hypothyroidism (CH) to prevent long-term cognitive and physical impairment. We report a case of a twin with CH missed by newborn screening using umbilical cord blood thyroid-stimulating hormone (TSH) in Malaysia. CASE A 13-year-old Malay female was born at 34 weeks of gestation with a birth weight of 1600 g. Her cord TSH screening was normal at birth (6.54 mIU/L). She is the first twin of monozygotic monoamniotic twins. Her larger twin sister weighed 2470 g at birth and also had normal cord TSH (3.12 mIU/L). The patient was admitted at birth for feeding establishment, nosocomial infection and neonatal jaundice. She presented later at 2 months of age with abdominal distension, constipation and lethargy, and was treated for sepsis. At 5 months of age, she was noted to have faltering growth, developmental delay, and constipation. Her growth parameters were way below the 3rd percentile (weight 3400 g, length 53 cm and head circumference of 34 cm) and she also had macroglossia and hypotonia. Thyroid function test (TFT) showed severe primary hypothyroidism (TSH 194 uIU/mL, free T4 <5.15 pmol/L). She was initiated on oral thyroxine 15 mcg/kg/day at 5 months of age and her TFTs normalized within a month of treatment. Ultrasound of the thyroid gland at 3 years of age revealed thyroid gland hypoplasia. Her twin had normal growth and development. CONCLUSION This case illustrates the need to retest the thyroid function in same-sex twins even when the cord TSH screening is normal. There should also be a high index of suspicion on the diagnosis of congenital hypothyroidism in infants with faltering growth, constipation, or developmental delay.